Desa Pekerja Bangunan: Pemberdayaan Masyarakat Menuju Desa Penghasil Pekerja Bangunan Profesional Dan Bersertifikat Dengan Pemasaran Jasa Online Di Kelurahan Gunungpati - Agustinus Sungsang Nana Patria; Dwi Sulistiyawati; Brian Dwi Riswanto; Tabita Vinesia Damai Yanti; Wafik Nur Maulina; Adibah Sulistiyoningsih; Fariha Fatmawati Rini Nur Aini; Noor Mohammad Hatta; Immanuel Elang Artha Putra; Aleda Elly; Kevin Dwi Andriansyah; Wisnu Rahmat Penjawi; Akhmad Amiq Sauqi Adhim (Universitas 45 Surabaya, 2023)
The needs of construction workers play a very important role in society. However, based on the results of a survey of several construction workers from Gunungpati Village, problems were found such as never having received socialization and training, not having a craftsman skills certificate, lack of interest in learning and literacy among the residents, not really knowing the construction workers from Gunungpati Village and marketing of construction worker services is still conventional. To answer these problems, PPK Ormawa BEM Faculty of Engineering, University of 17 August 1945 Semarang implemented construction worker empowerment programs in the Gunungpati sub-district such as the